Extensive bullous lichen sclerosus et atrophicus - Jelica Vukicevic (Sociedade Brasileira de Dermatologia, 2016)
Abstract Lichen sclerosus et atrophicus is a chronic disease of unknown etiology characterized by atrophic and sclerotic plaques in both genital and extragenital regions. Extensive bullous lichen sclerosus et atrophicus (BLSA) is a severe variant of the disease with no widely accepted treatment. We present a 63-year-old woman with extensive extragenital, ivory-colored, atrophic plaques on her trunk and extremities and disseminated hemorrhagic bullae. The patient was unsuccessfully treated with standard topical corticosteroid therapy, doxycycline and chloroquine. According to the literature, there is little evidence of the efficacy of doxycycline and hydroxychloroquine in the treatment of BLSA. We report a rare case of extensive BLSA that is unresponsive to these drugs.